Hydroxycinnamic acids in cooked potato tubers from Solanum tuberosum group Phureja - Piñeros‐Niño, Clara (Food Sci Nutr, 2016)
Hydroxycinnamic acids are phenolic compounds and are considered to have health promotion properties due to their antioxidant activity. Potato tubers of 113 genotypes of Solanum tuberosum group Phureja belonging to the Colombian Central Collection, landraces of potatoes, and commercial cultivars were evaluated for their hydroxycinnamic acids content. The composition of these compounds was analyzed using cooked tubers in two different agro‐climatic conditions. The genotypes were analyzed for chlorogenic acid, neo‐chlorogenic acid, crypto‐chlorogenic acid, and caffeic acid by ultrahigh‐performance liquid chromatography (UHPLC). Chlorogenic acid was the major representative and varied between 0.77 to 7.98 g kg(−1) DW (dry weight) followed by crypto‐chlorogenic acid (from 0.09 to 1.50 g kg(−1) DW). Under moorland agro‐climatic conditions even though the chlorogenic acid levels increased with respect to flatland agro‐climatic conditions, the related isomer neo‐chlorogenic acid decreased as compared to flatland conditions. The correlation between chlorogenic acid with the isomers, and with caffeic acid was positive. This study demonstrated that there is a wide variation in hydroxycinnamic acids contents in the germplasm studied, which can be exploited in breeding programs to contribute to human health.